DINAMIKA KOMUNIKASI PERILAKU CYBERBULLYING DI MEDIA SOSIAL FACEBOOK PADA REMAJA DI SMAN 2 SIDRAP (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
On Facebook social media, cyberbullying cases are very frequent, and most victims are unaware that they are victims, and many victims experience various social problems and in themselves due to a lack of education related to the case. This study aims to find out why a person can become a victim of cyberbullying, the form, and the factors that cause cyberbullying. The informant is a victim of cyberbullying on Facebook and attends SMAN 2 SIDRAP, selected by the side snowball method to obtain eight people. This research is qualitative using a phenomenological approach. Data was collected through observation, interviews, and documentation using data analysis using the Purposive Sampling method. From the results of this study, the researcher found that cyberbullying behavior on Facebook and social media in adolescents at SMAN 2 SIDRAP can help victims improve their privacy and control themselves, especially on social media. The factors that cause cyberbullying to occur are the characteristics of each individual and victim, the victim's social environment, and also the motivation of the perpetrator. This research is expected to be used to add new insights and make everyone aware of how cyberbullying can occur so that it can be avoided, as well as encourage every reader to be literate about cyberbullying and not underestimate it.